Occurrence of pharmaceuticals in a water supply system and related human health risk assessment. (1st April 2015) - de Jesus Gaffney, Vanessa; Almeida, Cristina M.M.; Rodrigues, Alexandre; Ferreira, Elisabete; Benoliel, Maria João; Cardoso, Vitor Vale
Abstract: A monitoring study of 31 pharmaceuticals along Lisbon's drinking water supply system was implemented, which comprised the analysis of 250 samples including raw water (surface water and groundwater), and drinking water. Of the 31 pharmaceutical compounds, only sixteen were quantified in the analyzed samples, with levels ranging from 0.005 to 46 ng/L in raw water samples and 0.09–46 ng/L in drinking water samples. The human health risk assessment performed showed that appreciable risks to the consumer's health arising from exposure to trace levels of pharmaceuticals in drinking water are extremely unlikely, as RQs values were all below 0.001. Also, pharmaceuticals were selected as indicators to be used as a tool to control the quality of raw water and the treatment efficiency in the drinking water treatment plants. Graphical abstract: Highlights: 31 pharmaceuticals were monitored in a Portuguese water supply system. A human health risk assessment was performed. Indicators that could be used as quality control tools were defined.